Prophylaxis Against Macular Edema Following YAG Laser Capsulotomy In Diabetic Patients (The Review of Diabetic Studies, 2024)
Background: Diabetic patients are at increased risk of developing macular edema following Nd:YAG laser posterior capsulotomy. Prostaglandin-mediated inflammation is believed to play a key role in this complication. Topical non-steroidal anti-inflammatory drugs (NSAIDs) may reduce postoperative inflammatory changes.Objective: To evaluate the efficacy of topical Nepafenac in the prophylaxis against macular edema following Nd:YAG laser capsulotomy in diabetic patients.Methods: This prospective, randomized interventional study included 80 eyes of 80 type II diabetic patients with visually significant posterior capsule opacification after uneventful phacoemulsification. Patients were randomly assigned into two groups: Group I received topical corticosteroids, alpha-adrenergic agonists for one week, and Nepafenac 0.1% for four weeks; Group II received only corticosteroids and alpha-adrenergic agonists. Best-corrected visual acuity (BCVA), perifoveal macular thickness (PMT), and intraocular pressure (IOP) were assessed preoperatively and at 1, 4, and 12 weeks’ post-procedure using spectral-domain OCT and standard ophthalmic examinations.Results: Both groups showed significant improvement in BCVA after capsulotomy. However, Group I demonstrated significantly better BCVA at 1 week (p = 0.003). PMT was significantly lower in the Nepafenac group at all postoperative follow-ups (p < 0.01), indicating reduced macular thickening. Transient IOP elevation occurred in both groups at 1 week, with no significant intergroup difference and spontaneous resolution thereafter.Conclusion: Prophylactic use of topical Nepafenac following Nd:YAG laser capsulotomy in diabetic patients effectively reduces perifoveal macular thickening and enhances early visual outcomes without affecting IOP. Routine NSAID prophylaxis is recommended in this high-risk population.